Ultrahigh Thermoelectric Performance in Environmentally Friendly SnTe Achieved through Stress‐Induced Lotus‐Seedpod‐Like Grain Boundaries. (28th May 2021) - Guo, Fengkai; Cui, Bo; Li, Chun; Wang, Yumei; Cao, Jian; Zhang, Xinghong; Ren, Zhifeng; Cai, Wei; Sui, Jiehe
Abstract: In an effort to improve the thermoelectric performance of the environmentally friendly SnTe, here, a multilevel structure composed of "lotus‐seedpod‐like" grain boundaries, dense dislocations, and nanopores is innovatively constructed, which synergistically reduces the sound velocity and the phonon relaxation time, resulting in ultralow lattice thermal conductivity throughout a wide temperature range. An ultrahigh figure of merit, ZT, of ≈1.7 and an unprecedented average ZT of ≈1 from 300 to 873 K are obtained. In contrast to the common pore‐forming method of volatilization, the strategy of stress‐induced recrystallization and gas expansion cogenerating interfacial pores that is used here, is believed to be more widely applicable for many other materials, which opens up a new avenue for improving thermoelectric performance. Abstract : A "lotus‐seedpod‐like" grain boundary is constructed utilizing stress‐induced recystallization and trapped gas expansion in Mn‐doped SnTe. This structure decouples the transmission of charge carriers and phonons. A superhigh ZT of ≈1.7 at 873 K and a record ZT ave of ≈1 between 300 and 873 K are realized.